Growth rings in roots of medicinal perennial dicotyledonous herbs from temperate and subtropical zones in China. Issue 4 (11th January 2018) - Chu, Shanshan; Tan, Lingling; Liu, Chanchan; Peng, Huasheng; Duan, Haiyan; Huang, Luqi
Abstract: Growth years are closely related to the quality of Chinese medicinal materials, and they can provide a reliable basis for quality evaluation on crude drugs in accordance with the suitable growth years. Herbchronology, the numerical and pattern analysis of annual growth rings in herbaceous perennials, has emerged to be a recognized science that is applied in age determination of perennial forbs. Fifty medicinal species growing in temperate and subtropical zones of China were examined by microstructure observation to determine the presence of growth rings in the secondary root xylem of medicinal perennial dicotyledonous herbs. Nearly half of the surveyed species showed clearly or relatively clearly demarcated growth rings in their roots, and additional anatomical patterns have been observed in different species. Clear variations in growth rings of different genus or species were characterized in this study, and these findings proved the feasibility of applying herbaceous plant growth rings in age identification of traditional Chinese medicine. Abstract : Growth rings in the roots of 50 medicinal herbs were examined by microstructure, and variations in growth rings of different genera or species were characterized. The results showed that herbaceous plant growth rings could be applied in age identification of traditional Chinese medicine.